Penerapan GAP dan Tumpang Sari Cabai–Nilam untuk Rehabilitasi Lahan Marginal dan Peningkatan Produktivitas di Desa Lambadeuk, Aceh Besar - Mujiburrahmad, Mujiburrahmad; Agussabti, Agussabti; Elviani, Elviani; Zohra, Zohra; Nurhasanah, Putri; Manyamsari, Ira (Yayasan Kawanad, 2025)
This community service program was conducted in Lambadeuk Village, Peukan Bada District, Aceh Besar Regency, aiming to enhance the productivity of marginal land through the application of Good Agricultural Practices (GAP) and a chili–patchouli intercropping system. The area is dominated by Entisol soils characterized by low fertility, compact structure, and limited water availability. Two farmer groups were selected as partners based on their land ownership, activeness, and commitment to participate throughout the program. The activities included socialization, technical training, field practice, and continuous mentoring. The training materials covered liquid organic fertilizer preparation, mycorrhiza application, integrated pest management, and intercropping techniques. Results indicated noticeable improvement in soil physical properties following organic fertilizer and mycorrhiza application. The soil became looser in texture, darker in color, and visibly richer in organic matter. The patchouli plant survival rate reached 62.5%, and no significant pest attacks were recorded. Active participation of farmers in all stages demonstrated an increase in technical knowledge and practical skills related to sustainable farming. These findings suggest that integrating GAP with organic and biological soil amendments can serve as an effective approach to revitalize marginal lands and strengthen farmers’ capacity toward a more resilient and productive agricultural system.